The role of psychological stress in the pathogenesis of psoriasis - Dongyun Lei; Canyi Gong; Bin Wang; Litao Zhang; Guoqiang Zhang; Guoqiang Zhang; Mao-Qiang Man (Frontiers in Medicine)
Psoriasis is an immune-mediated dermatosis characterized by systemic inflammation and multifactorial pathogenesis. Among its many triggers, psychological stress has emerged as a pivotal yet underappreciated contributor to disease onset and exacerbation. Although the pathomechanisms by which psychological stress is involved in the pathogenesis of psoriasis are not clear, evidence suggests a regulatory role of psychologic stress in immune functions, including increasing expression levels of proinflammatory cytokines and intracellular adhesion molecule-1 (ICAM-1), and decreasing anti-inflammatory cytokines and the function of glucocorticoid receptors, possibly in part via activation of corticotropin-releasing hormone (CRH)-proopiomelanocortin (POMC)-adrenocorticotropic hormone (ACTH)-corticosteroids axis. In addition, the onset and/or worsening of psoriasis can also be attributed to psychological stress-induced defective epidermal permeability barrier function. Moreover, the bidirectional nature of this relationship often leads to a vicious cycle of flare-ups and psychological distress, further complicating patient management and quality of life. This review aims to synthesize current evidence on the relationship between stress and psoriasis, examining mechanistic pathways through which psychosocial stress contributes to immune dysregulation in psoriatic pathology. It also underscores the significance of psychological interventions in the management of psoriasis.